2008
DOI: 10.2485/jhtb.17.1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Growth (ING) Family: An Emerging Molecular Target for Cancer Therapy

Abstract: ING1 gene, the founding member of the ING tumor suppressor family, was originally identified through subtractive hybridization between normal mammary epithelial cells and breast cancer cell lines, and subsequent in vivo selection of genetic suppressor element that displayed oncogenic features. Soon after identification of ING1, four additional members of the ING family (ING2-5) were cloned and all the gene products contain a highly conserved plant homeodomain (PHD) finger motif in the carboxy (C)-terminal end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…A large body of research has shown evidence for alteration or down-regulation of the ING genes in malignancies [2][3][4]. ING2 was shown to be down-regulated at both the transcriptional and posttranslational levels and was closely associated with a poor survival rate in hepatocellular carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A large body of research has shown evidence for alteration or down-regulation of the ING genes in malignancies [2][3][4]. ING2 was shown to be down-regulated at both the transcriptional and posttranslational levels and was closely associated with a poor survival rate in hepatocellular carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ING5 is localized to human chromosome 2q37.3, contains 8 exons and 7 introns, and encodes 5233-bp cDNA, whose 1068 nucleotides are translated into 28-kDa protein of 240 amino acids [2]. The encoding product, a tumor suppressor protein, can inhibit cell growth and induce apoptosis [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations